2015
DOI: 10.3109/13880209.2015.1040515
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, antimicrobial and wound healing properties ofStruthanthus vulgaris

Abstract: Context: Struthanthus vulgaris (Vell.) Mart. (Loranthaceae) has been widely used in traditional medicine in Brazil to bathe wounds. Objective: The objective of this study is to investigate the in vitro wound healing effects, together with the antioxidant and antimicrobial activities of S. vulgaris leaf and branch extracts. Material and methods: Ethanol leaf and branch extracts of S. vulgaris were investigated at 1-100 mg/ml concentrations in the scratch assay after 14 h. Antioxidant activity was investigated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 42 publications
2
38
0
1
Order By: Relevance
“…Therefore, the well-formed collagen fibers observed in S. vulgaris treated group by histomorphometric analysis and biochemical determination of hydroxyproline could support the S. vulgaris effectiveness in fibroblastic proliferation and synthesis the extracellular matrix during wound healing. Corroborating to our results, Vittorazzi et al, (2015) demonstrated the in vitro beneficial effects of S. vulgaris in wound healing processes by its ability to stimulate the migration and proliferation of fibroblast in the wound scratch assay. Furthermore, stimulation of epithelial cell proliferations are vital for wound healing to take place.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Therefore, the well-formed collagen fibers observed in S. vulgaris treated group by histomorphometric analysis and biochemical determination of hydroxyproline could support the S. vulgaris effectiveness in fibroblastic proliferation and synthesis the extracellular matrix during wound healing. Corroborating to our results, Vittorazzi et al, (2015) demonstrated the in vitro beneficial effects of S. vulgaris in wound healing processes by its ability to stimulate the migration and proliferation of fibroblast in the wound scratch assay. Furthermore, stimulation of epithelial cell proliferations are vital for wound healing to take place.…”
Section: Discussionsupporting
confidence: 73%
“…The biological observed effects were attributed to the presence of flavonoids, condensed tannins (proanthocyanidins) and saponins in the leaf extract (Vieira et al, 2005). Recently, Vittorazzi et al (2015) showed the antioxidant and antibacterial activities of S. vulgaris together with the in vitro stimulatory effects on proliferation and migration of fibroblasts.…”
Section: Struthanthus Vulgarismentioning
confidence: 96%
See 1 more Smart Citation
“…The In vitro proliferative activity was evaluated in the colorimetric MTT assay [28]. Exponential growing L929 Mouse fibroblast cells were plated in 96-well micropates at a density of 5 × 10 3 cells per well in 100 μL of culture medium and were allowed to adhere for 16 h, cultured in a humidified atmosphere at 37 °C in 5% CO2 before treatment.…”
Section: Assessment Of In Vitro Proliferative Activitymentioning
confidence: 99%
“…These components prevent blood and lymph accumulation by regulating micro vessels around the wound lesion area and thus reduce local swelling. They also improve blood circulation and enhance continuous perfusion to facilitate the healing of wound lesions (22,23). Since the most important class of active ingredients present in Crataegus sp.…”
Section: Discussionmentioning
confidence: 99%